Treatment for Open Limb Compression Injury: Clinical and Experimental Study - V. V. Semchenko; A. V. Klementyev; S. S. Stepanov; G. F. Sobolev; A. E. Mangus (Общая реаниматология, 2008)
The study has experimentally and clinically ascertained the efficiency of co-administration of propofol and perfluo-rane in the acute period after brain injury. An experimental morphological study has established that the combined use of the test agents diminishes the magnitude of brain tissue damages and positively affects the angio-, cyto-, and synaptoarchitectonics of the cerebral cortex in the posttraumatic period. Based on the analysis of the absolute and relative risks of poor outcome; intracranial hypertension; systemic cerebral and focal neurological disorders; displacement and dislocation of cerebral structures; blood hyperosmolarity; hyperglycemia; creatinemia; uremia; anemia; positive or negative cognitive changes by the Glasgow coma scale; changes in vital functions; as well as the efficiency of performed therapy, the clinical study has established that the co-administration of propofol and perfluorane improves postoperative brain function recovery. The total results of the experimental and clinical studies may be regarded as a rationale for the expediency of co-administering propofol and perfluorane to be included into the complex treatment of patients with severe brain injury.